Blueprint to boost marketability of grads: Khaled - Daily Express, (KK) (Daily Express (kk), 2012)
SEPANG: The Government on Tuesday launched the Graduate Employability Blueprint for 2012-2017 that will focus on boosting the level of graduate marketability as well as fulfilling the needs of the professional and skilled manpower towards national development.